Staging Multicultural Values and Tolerance through Genre in an Indonesian EFL Textbook - Martria, Mayang; Kalsum, Kalsum; Bahtiar, Bahtiar; Yusuf, Muh. (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This study explores how multicultural values and tolerance are discursively constructed through genre in an Indonesian EFL textbook. It focuses on English for Nusantara Student’s Book for SMP/MTs Grade VIII, a nationally distributed textbook used in junior secondary education, including Madrasah Tsanawiyah Negeri (MTsN). Employing qualitative content analysis, the study examines 49 verbal and visual text units across dialogue, narrative, recount, report, and procedure genres through the lens of Systemic Functional Linguistics genre theory and multicultural education. The findings reveal that multicultural values and tolerance are not uniformly presented across the textbook; rather, they are staged differently through genre. Dialogue, narrative, and recount tend to humanize difference through empathy, shared experience, and moral evaluation, while report and procedure tend to normalize diversity through knowledge, social awareness, and practical action. The study contributes to EFL textbook research by demonstrating that values are not only thematically represented but also genre-shaped in ways that influence how learners are invited to understand and practice tolerance. The findings have implications for the design of English teaching materials in diverse educational settings.